Inside Photoshop CS - Bouton, Gary David, 1953- (SAMS Pub., 2004)
Gary Bouton has made Inside Photoshop CS a perennial best-seller due to the loyalty of his audience. A lot of people simply love the way Gary explains what Photoshop is all about. In this revised edition, Gary truly puts the outsider "inside", demystifying such intangibles as pixels, color wheel, resolution, line screens, and more of vital information for the hobbyists and professional. He covers all the new features and adds expert tips and tricks for the digital photographer. Critics and readers alike have noted that Bouton's writing style makes difficult, technical topics easy to understand -- as if they were being guided by a close friend or mentor.